On some \(BV_σ\) I-convergent sequence spaces defined by modulus function - Khan, Vakeel.A.; Esi, Ayhan; Shafiq, Mohd (Global Journal of Mathematical Analysis, 2014)
In this article we introduce and study \(_{0}BV^I_σ(f)\), \(BV^I_{σ}(f)\) and \(_{∞}BV^I_{σ}(f)\) sequence spaces with the help of \(BV_σ\) [see [23]] and a modulus function $f$. We study topological, algebraic properties and some inclusion relations on these sequence spaces.